2013
DOI: 10.1590/s0100-40422013000700016
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic response induced by endophytic fungi and bacteria in H. marrubioides Epling in vitro microplants

Abstract: Hyptis marrubioides Epling is a native plant from Brazilian Cerrado. In this paper, the response of in vitro microplants of this species to inoculation with bacterial and fungal endophytic isolates is evaluated. HPLC-DAD analysis showed the presence of 3,4-O-(Z)-dicaffeoylquinic acid and quercetin-7-O-glucoside as the main components. GC/MS analysis demonstrated that the sesquiterpenes t-cadinol and caryophyllene oxide were only produced in microplants inoculated with endophytic bacteria, while methyl hexadeca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Two chemical analysis techniques used in metabolic profiling include 1 H nuclear magnetic resonance (NMR) spectroscopy and high-performance liquid chromatography (HPLC). For instance, high-performance liquid chromatography - diode array detector (HPLC-DAD) analysis showed the presence of 3,4-O-( Z )-dicaffeoylquinic acid and quercetin-7- O -glucoside as the main components from in vitro microplants of Hyptis marrubioides Epling inoculated with bacterial and fungal endophytic isolates [ 11 ]. Similarly metabolomic methods such as these can be effective to decipher the potential involvement of endophytic fungi in the production of secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Two chemical analysis techniques used in metabolic profiling include 1 H nuclear magnetic resonance (NMR) spectroscopy and high-performance liquid chromatography (HPLC). For instance, high-performance liquid chromatography - diode array detector (HPLC-DAD) analysis showed the presence of 3,4-O-( Z )-dicaffeoylquinic acid and quercetin-7- O -glucoside as the main components from in vitro microplants of Hyptis marrubioides Epling inoculated with bacterial and fungal endophytic isolates [ 11 ]. Similarly metabolomic methods such as these can be effective to decipher the potential involvement of endophytic fungi in the production of secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…17 Natural products synthesized by endophytic bacteria can induce resistance to plant pathogens 18 or biocontrol phytopathogens by lipopeptides that result in plant growth. 19 Previous studies by our research group 20 found that the endophytes colonization of Hyptis marrubioides seedlings Epling results in a qualitative and quantitative modification of the phytochemical profile of the host. In this study, we decided to investigate the relationship of V. divergens and their endophytic fungi collected in dry and wet seasons in Pantanal.…”
Section: Introductionmentioning
confidence: 96%
“…The interaction between plants and microorganisms may be either beneficial (mutualism) or detrimental (parasitism) to the health of the plant. In this context, endophytes are an important group of microorganisms, able to interact with the host plant via a mutually beneficial mechanism without visible symptoms of the fungal colonization [3] . The synergy between endophytic fungi and their host plant can promote morphological, physiological and biochemical changes through the expression of bioactive metabolites, increasing the plant's resistance to biotic and abiotic stresses [4] …”
Section: Introductionmentioning
confidence: 99%
“…In this context, endophytes are an important group of microorganisms, able to interact with the host plant via a mutually beneficial mechanism without visible symptoms of the fungal colonization. [3] The synergy between endophytic fungi and their host plant can promote morphological, physiological and biochemical changes through the expression of bioactive metabolites, increasing the plant's resistance to biotic and abiotic stresses. [4] Diversity of chemical structures is demonstrated through metabolite composition such as metabolite class and its concentration.…”
Section: Introductionmentioning
confidence: 99%